2017
DOI: 10.1002/cjce.22757
|View full text |Cite
|
Sign up to set email alerts
|

Bed diameter effect on the hydrodynamics of gas‐solid fluidized beds via radioactive particle tracking (RPT) technique

Abstract: The hydrodynamics observed in large‐scale gas‐solid fluidized bed reactors are different from those observed in smaller scale beds. In this study, the effect of bed diameter on the hydrodynamics of gas‐solid fluidized bed reactors has been investigated in two bubbling fluidized beds of 44 cm and 14 cm in diameter using an advanced non‐invasive radioactive particle tracking (RPT) technique. Compressed air at room temperature was used as the gas phase, and the solid was glass beads with a particle size of 210 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The green cluster above overlaps and shares many of the techniques with the blue cluster, as evidenced by the lines that represent co‐citation links. Particle size distribution (PSD), thermal gravimetric analysis (TGA), scanning electron microscopy (SEM), and Fourier‐transform infrared spectroscopy (FTIR) are prominent in the cluster . The other techniques mostly relate to particle characterization (AAS, EDX, DSC, UPS) …”
Section: Introductionmentioning
confidence: 99%
“…The green cluster above overlaps and shares many of the techniques with the blue cluster, as evidenced by the lines that represent co‐citation links. Particle size distribution (PSD), thermal gravimetric analysis (TGA), scanning electron microscopy (SEM), and Fourier‐transform infrared spectroscopy (FTIR) are prominent in the cluster . The other techniques mostly relate to particle characterization (AAS, EDX, DSC, UPS) …”
Section: Introductionmentioning
confidence: 99%
“…Figure and Figure exhibit schematic and photographic images of the CT technique with a bubble column equipped with a bundle of vertical internals. The CT technique has been successfully applied to measure the phase holdup distribution in different multiphase flow reactors with various scale sizes at mReal such as 12 in (0.3 m) pebble bed reactor, 6 in (0.152 m) bubble column, 6 in (0.152 m) and 18 in (0.46 m) fluidized beds, and 3 in (0.076 m) and 6 in (0.152 m) spouted bed reactors . Details on the mechanical design, hardware, software, and operation of the CT technique have been discussed elsewhere by Varma .…”
Section: Gamma‐ray Computed Tomography (Ct)mentioning
confidence: 99%
“…Ettehadieh et al 40 previously showed a centimeter‐sized jet makes the axial solid hold‐up uniform for Geldart D particles by increasing the solid diffusivity in this direction. However, since the radial solid diffusivity is constant for small bed diameters, 41 the bed remains almost uniform in the radial directions at all gas velocities. In this regime, the general patterns of solid hold‐up variations identified at U mf remain, but at proportionally lower solid hold‐up values as a result of introducing more fluidizing gas to the system.…”
Section: Resultsmentioning
confidence: 99%